MAXILLOFACIAL TRAUMA: CURRENT PRACTICE IN MANAGEMENT AT PAKISTAN INSTITUTE OF MEDICAL SCIENCES - Hussain, S. Shahid; Ahmad, Muhammad; Khan, M. Ibrahim; Anwar, Muhammad; Amin, Mughese; Ajmal, Sameera; Tariq, Farhan; Ahmad, Naheed; Iqbal, Tariq; Malik, Saleem A. (Journal of Ayub Medical College Abbottabad, 2003)
Background: This study was carried out to determine the aetiology, pattern and management of maxillofacial injuries at PIMS, Islamabad. Methods: This descriptive study was conducted at Plastic Surgery Department, PIMS Islamabad from 1st February 1998 to 30th April 2002. All the adult patients presenting with maxillofacial injures were included where as patients less than 12 years of age and only facial lacerations were excluded. Similarly isolated nasal bone fractures were also excluded because these patients were routinely managed by ENT department. Age, sex, presentation, aetiology, associated injuries and treatment modalities undertaken in these patients were recorded. RESULTS: In 164 patients 254 fractures were noted. Most were male (86%), ranging in age from 13-71 years with a male to female ratio of 6:1 respectively. The most frequent (48%) cause noticed was road traffic accidents followed by assault. Mandible was the commonest to be involved in such injuries followed by maxilla. Most of the patients (32%) had associated facial injuries. Various treatment modalities were practiced. Conclusion: Maxillofacial fractures should be managed by open reduction and internal fixation as early as possible. Key Words: Maxillofacial, Trauma, Mandible, Management